Accounting For Developmental Transactions - Suhendar, Fikry Ramadhan; Shofa, Fauziah Mutiara (Pascasarjana STIE Miftahul Huda, 2024)
With this piece, I want to give a little insight into how the Islamic economic system operates on the accounting of musyarakah transactions. This essay employs a qualitative approach to research. This information comes from books and some of the results of research on the internet that explain the accounting of musyarakah transactions. This article relies on qualitative information. In this piece, we use a narrative approach to analyzing the data. The accounting of musyarakah transactions is the process of financial transactions used by the general public. The accounting itself has the sense of an art of filing, grouping, compiling of a financial report. Transactions are a system that people use when it comes to buying and selling. Musyarakah is a common form of business done by two people and the result is equally divided.